Beneficial effect of diverse fermentation treatments on nutritional composition, bioactive components, and anti-nutritional factors of foxtail millet (Setaria italica L.) - Jan, Sumaira; Kumar, Krishan; Ahmed, Naseer; Thakur, Priyanka; Chauhan, Divya; Rizvi, Qurat-Ul Eain Hyder; Vyas, Pritesh (Journal of Postharvest Technology, 2022)
The foxtail millet (Setaria italica L.) flour was exposed to lactic acid fermentation by using two strains of Lactobacillus i.e. with Lactobacillus  brevis (BF) and Lactobacillus plantarum (PF), yeast (Saccharomyces cerevisiae L.) (YF), yeast + ammonium sulfate [(NH4)2SO4] (YAF) and  combined treatment of yeast and L. brevis (CF) at an interval of 12, 24 and 36 h. The samples after drying were evaluated for their nutritional,  anti-nutritional, minerals, and bioactive components. The total phenolics enhanced significantly (p≤0.05) during all fermentation treatments but  the highest value was observed during YAF treatment. Similarly, the antioxidant activity improved significantly (p≤0.05) during all treatments  but the highest values were observed during YAF treatment. The fermentation treatments increased significantly (p≤0.05) the crude protein  content during all fermentation treatments. Whereas, there was a significant (p≤0.05) decrease in crude fiber and fat content. A significant  (p≤0.05) increase in mineral contents such as Cu, Fe, Mn, and Zn was observed after all fermentation treatments. Anti-nutrients such as phytic  acid declined significantly (p≤0.05) during all fermentation treatments but the highest reductions were observed during treatment with L. brevis (BF) and with yeast + (NH4)2SO4 (YAF). Similarly, the tannin contents reduced significantly (p≤0.05) during all fermentation treatments. The  results concluded that fermentation could be the most efficient technique of improving the bioactive compounds, nutritional components, and  antioxidant activity of foxtail millet flour with a significant reduction in anti-nutritional components.
Keywords: Anti-nutrients; fermentation; Lactobacillus brevis; Lactobacillus plantarum; Saccharomyces cerevisiae